Effect of kinaesthetic tapes on plantarflexor muscle performance - Csapo, R.; Herceg, M.; Alegre, L.; Crevenna, R.; Pieber, K. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Kinaesthetic tapes (KT) are frequently used in physiotherapy and sports medicine to improve circulation of blood and lymph flow, relieve pain through neurological suppression, or enhance proprioception by cutaneous stimulation of peripheral afferent nerves. In addition to these therapeutic objectives, it has been suggested that KT-application may enhance motoneuron activity, purportedly facilitating contraction and increasing muscle strength (Hammer, 2006). However, studies performed to validate the proposed performance-enhancing effects have yielded controversial results (Vithoulka et al., 2010; Fu et al., 2008). The purpose of this study was to examine the effects of application of KT on plantarflexor muscle performance in different motor tasks. We hypothesised that taping of the triceps surae muscle would improve isometric plantarflexor strength and muscular endurance with no significant effect on drop jump performance. Methods: Using a repeated-measures design, all performance measures were obtained in 12 male (age: 24.9±4.0 yrs; height: 1.80±0.06 m; mass: 74.0±6.2 kg) and 12 female (age: 24.0±3.6 yrs; height: 1.67±0.04 m; mass: 61.1±5.9 kg) participants on two separate occasions: without tapes (NT) and after application of KT over the triceps surae muscle. Isometric plantarflexor strength was measured by Biodex dynamometry. During strength tests, integrated electromyographic activity (iEMG) was obtained from both heads of the gastrocnemius muscle. To determine muscular endurance, participants completed an isokinetic fatigue test (30 consecutive contractions at 180°/s). Drop jump performance (jump heights and ground contact times) was assessed in a series of jumps from different drop heights (20, 40 and 60 cm), analysing the vertical components of ground reaction forces. Results: The KT-intervention was associated with a general increase in gastrocnemius iEMG activity. However, significant increases in isometric strength were only found at fully dorsiflexed ankle positions (KT: 155.2±42.0 Nm vs NT: 140.5±51.5 Nm, p = 0.037). Strength gains were negatively correlated to baseline strength (r = -0.58, p = 0.003). In the isokinetic fatigue and drop jump tests, no significant differences were observed between NT- and KT-conditions. Discussion: The application of KT over the triceps surae muscle promotes an increase in isometric strength and gastrocnemius iEMG activity. Our data suggest that these effects are joint-angle dependent and more prominent in weaker individuals. By contrast, the KT-intervention does neither improve drop jump performance nor muscular endurance.